Effects of flexi-bar training on muscle strength and physical performance in older people with dynapenia: the protocol of a randomised controlled trial - Xinxin Wang; Ning Wei; Mengyu Lyu (BMJ Open)
Introduction Dynapenia is a new term that is used to describe the age-related loss of muscle strength. Flexi-bar training is a safe and feasible device for older people with dynapenia. This study will investigate the effects of a 12-week flexi-bar training programme on muscle strength and physical function in older people with dynapenia.Methods and analysis A total of 114 participants (aged more than 65 years) with age-related muscle loss will participate in a 12-week flexi-bar training programme. The participants will be randomly divided into three groups, namely, flexi-bar, placebo and control, with equal number of participants in each group. The assessments will be conducted at preintervention, postintervention and 12 weeks after training completion. The primary outcome is timed-up-and-go test. The secondary outcomes are five-repetition sit-to-stand test, 10-metre walking test, handgrip strength, as well as the serum albumin and haemoglobin levels.Ethics and dissemination The procedures of this study were reviewed and approved by the Human Ethics Review Board of Wuhan Brain Hospital (General Hospital of the Yangtze River Shipping) on 29 September 2020 (#L20200013). The findings of this study will be published in peer-reviewed journals and presented at conferences. The trial was registered on 6 November 2020.Trial registration number ISRCTN14316668.